Penguatan Perilaku Rasional Politik Birokrasi (ASN, Kepala Desa Beserta Perangkat Desa) Di Kecamatan Kabila Dan Kecamatan Bulango Timur - Mahmud, Ramli; Adjie, Zulfikar; Wantu, Asmun; Yunus, Rasid (Universitas Pahlawan Tuanku Tambusai, 2024)
The tendency for the bureaucracy to not be neutral in the election arena is caused by the bureaucracy's political behavior patterns. Political behavior in sociological and party approaches makes these policies patterned at segmentation of religious groups, ethnicities, political parties and so on. Bureaucratic neutrality can be achieved if the political preferences of the bureaucracy (ASN, Village Head, Village Apparatus) are influenced by rational political behavior. This service aims to 1) Identify problems of vulnerability to election violations that occur around the environmental bureaucracy, 2) Build awareness of the bureaucracy to continue working to overcome types of election violations. 3) Provide enforcement of rational political behavior values ​​in supporting bureaucratic neutrality in elections. 4) As a means of political education to strengthen the preferences of the political bureaucracy so that they become intelligent voters and actively participate in supervising the 2024 simultaneous elections. Through this service, the bureaucracy can play a massive active role in carrying out participatory supervision ahead of the 2024 simultaneous elections.